Dispersing nano- and micro-sized portlandite particulates via electrosteric exclusion at short screening lengths. Issue 14 (20th March 2020) - Timmons, Jason; Mehdipour, Iman; Gao, Shang; Atahan, Hakan; Neithalath, Narayanan; Bauchy, Mathieu; Garboczi, Edward; Srivastava, Samanvaya; Sant, Gaurav
Abstract : Coulombic repulsion alone is insufficient to mitigate aggregation of suspensions with strong charge screening, while superior interparticle separations are created via steric hindrance when dispersant layer thickness exceeds the Debye length. Abstract : In spite of their high surface charge (zeta potential ζ = +34 mV), aqueous suspensions of portlandite (calcium hydroxide: Ca(OH)2 ) exhibit a strong tendency to aggregate, and thereby present unstable suspensions. While a variety of commercial dispersants seek to modify the suspension stability and rheology ( e.g., yield stress, viscosity), it remains unclear how the performance of electrostatically and/or electrosterically based additives is affected in aqueous environments having either a high ionic strength and/or a pH close to the particle's isoelectric point (IEP). We show that the high native ionic strength (pH ≈ 12.6, IEP: pH ≈ 13) of saturated portlandite suspensions strongly screens electrostatic forces (Debye length: κ −1 = 1.2 nm). As a result, coulombic repulsion alone is insufficient to mitigate particle aggregation and affect rheology. However, a longer-range geometrical particle–particle exclusion that arises from electrosteric hindrance caused by the introduction of comb polyelectrolyte dispersants is very effective at altering the rheological properties and fractal structuring of suspensions. As a result, comb-like dispersants that stretch into the solvent reduce the suspension's yield stress by 5× at similar levels of adsorption as compared to linear dispersants, thus enhancing the critical solid loading ( i.e., at which jamming occurs) by 1.4×. Significantly, the behavior of diverse dispersants is found to be inherently related to the thickness of the adsorbed polymer layer on particle surfaces. These outcomes inform the design of dispersants for concentrated suspensions that present strong charge screening behavior.